2020
DOI: 10.1186/s12885-020-6545-9
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and CD4 are independent prognostic factors for overall survival in endometrial carcinomas

Abstract: Background Tumor microenvironment (TME) including the immune checkpoint system impacts prognosis in some types of malignancy. The aim of our study was to investigate the precise prognostic significance of the TME profile in endometrial carcinoma. Methods We performed immunohistochemistry of the TME proteins, PD-L1, PD-1, CD4, CD8, CD68, and VEGF in endometrial carcinomas from 221 patients. Results High PD-L1 in tumor cells (TCs) was associated with better OS (p = 0.004), whereas high PD-L1 in tumor-infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…However, there were some discrepancies in the prognostic value of PD-L1 for endometrial carcinoma in previous studies. Zhang et al, 2020 [31] reported that high PD-L1 in TCs was associated with better overall survival, while high PD-L1 in TICs was associated with worse overall survival. In contrast, Engerud et al, 2020 [32] reported that PD-L1 expression in tumour cells was significantly associated with higher grade tumours, with no association with overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were some discrepancies in the prognostic value of PD-L1 for endometrial carcinoma in previous studies. Zhang et al, 2020 [31] reported that high PD-L1 in TCs was associated with better overall survival, while high PD-L1 in TICs was associated with worse overall survival. In contrast, Engerud et al, 2020 [32] reported that PD-L1 expression in tumour cells was significantly associated with higher grade tumours, with no association with overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, EC was found to have the highest prevalence of MSI of 30 tumor types. About 30% of primary EC are MSI-H, whereas 13% to 30% of recurrent EC are MSI-H or MMRd [39,[46][47][48][49].…”
Section: Cellular and Molecular Regulation Of Endometrial Cancer Progmentioning
confidence: 99%
“…One report showed that POLE-ultramutated and MSI-H EC tumors also have an overexpression of PD-L1 [46]. Interestingly, there is still great debate concerning the interpretation and relevance of PD-L1 expression on immune or tumor cells across several tumor types and its relationship to ICI efficacy in cancer [55].…”
Section: Cellular and Molecular Regulation Of Endometrial Cancer Progmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of ECs that are positive for PD-L1 expression varied from 14 to 59% (Mo et al, 2016;Li et al, 2018;Engerud et al, 2020). Although it was reported that PD-L1 expression has no significant impact on patient survival (Engerud et al, 2020), recent studies presented contrary results showing that higher PD-L1 expression in EC samples was associated with improved survival (Yamashita et al, 2017;Liu et al, 2019;Zhang et al, 2020). Also, increased PD-L1 expression in EC cells was significantly correlated with well-differentiated histology and a lower risk of myometrial invasion and lymphatic spread (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%